(untitled) (Fiep Bulletin - online, 2012)
It was a retrospective descriptive study designed to evaluate the weaning from mechanical ventilation in the Intensive Care Unit for adults at the University Hospital of the West of Paraná (HUOP), within one year. The study included 161 patients, mean age 47.5 ± 19.04 years. The mean APACHE II score was 22. The average number of days in the ICU was 11.63 ± 10.62 days. Regarding the length of invasive mechanical ventilation (IMV) on both days and hours was 9.27 ± 8.92 and 222.59 ± 213.67 respectively. One hundred and two (63%) patients were weaned on a first event with an average of 35.6 ± 45.2 hours. The predominant mode of weaning SIMV was associated with pressure support. Regarding the failure of extubation, 12% of patients had to be reintubated in a period ? 48 hours. There was great variability in the observed modes used and the choice of parameters for the completion of weaning from MV, suggesting, then, the presence of a routine service in the realization of this process. It was also found that the use of SIMV + PS weaning not extended the period of hospitalization of patients, even with other similar studies on the clinical severity of patients